Development and User Experiences of a Novel Virtual Reality Task for Poststroke Visuospatial Neglect : Exploratory Case Study - Danso, Andrew; Nijhuis, Patti; Ansani, Alessandro; Hartmann, Martin; Minkkinen, Gulnara; Luck, Geoff; Bamford, Joshua S.; Faber, Sarah; Agres, Kat R.; Glasser, Solange; Särkämö, Teppo; Rousi, Rebekah; et al. (JMIR Publications, 2025)
Background: Visuospatial neglect (VSN) affects spatial awareness, leading to functional and motor challenges. This case study explores virtual reality (VR) as a potential complementary tool for VSN rehabilitation. Objective: Specifically, we aim to explore the initial experiences of patients and physiotherapists engaging with a novel protocol, using an audiovisual cue task to support VSN rehabilitation. Methods: A preliminary VR task integrating audiovisual cues was co-designed with 2 physiotherapists. The task was then tested with 2 patients with VSN over 12 sessions. The intervention focused on engaging neglected spatial areas, with physiotherapists adapting the task to individual needs and monitoring responses. Results: Initial testing with 2 trainee physiotherapists indicated high usability, engagement, and perceived safety. Two patients with VSN completed 12 VR sessions. For Patient A, completion times increased following the introduction of an audio cue, though modeling indicated a nonsignificant linear trend (β=0.08; P=.33) and a marginally significant downward curvature (β=−0.001; P=.08). In contrast, Patient B showed a significant linear decrease in completion times (β=−0.53; P=.009), with a quadratic trend indicating a performance minimum around session 10 (β=0.007; P=.04). Intraweek variability also decreased. Motor scores (Box and Block Test and 9-Hole Peg Test) remained stable, and subjective feedback indicated improved mobility confidence and positive task engagement. Conclusions: Further research with larger cohorts is needed to confirm the VR task’s utility and refine the intervention.
Keywords: virtual reality; visuospatial neglect; physiotherapy training; audiovisual cues; patient experience; case report; fi=Viestintätieteet|en=Communication Studies|